Consolidation Model Recommendation for Rice Distribution in Indonesian Bureau of Logistics (West Java Regional Division) - Setiawan, Fran; Pratiwi, Loren; Wigono, Elisa Ferdilia (Jurnal Ilmiah Teknik Industri, 2020)
BULOG (Indonesian Bureau of Logistics) Regional Division West Java is a state-owned public company that regulates and maintains a supply of rice in order to meet the needs of all Indonesian people. Currently, BULOG distributing rice from one SubDivre warehouse to another SubDivre warehouse (point-to-point system) so shipping costs are higher because the frequency of transportation used is higher and the total distance traveled is higher. To reduce the cost of distribution, we propose consolidation model based on hub and spoke network topology. Hub and spoke system is done by determining which points become the hubs and which points become the spoke. The problem in determining the location of the hub and spoke is known as the hub location problem. In this problem, single allocation p-hub median problem is used. We use AMPL to get the solution. Various number of hubs (5,6,7) are tested and evaluated based on total shipping cost. The number of hubs which gives the minimum total shipping cost is 7. Delivery system using the hub and spoke network model can reduce the total cost of distribution by 13,94%.